Variability and genetic gain prediction for maintainer line improvement of hybrid rice in Bangladesh - Quddus , M R; Qayum, M A; Lipi, L F; Akter, A; Kulsum, M U; Islam, M S; Hasan, M J (Bangladesh Rice Journal, 2023)
Assessment of genetic variability in the nursery of the breeding population is essential for crop improvement successfully. Thirteen (13) maintainer lines of hybrid rice were evaluated to estimate the level of their genetic diversity and heritability of grain yield influencing parameters in the transplanted Aman, 2020 season. The studied traits were days to 50% flowering, total effective tillers plant-1, plant tallness (cm), length of flag leaf (cm), breadth of flag leaf (cm), panicle size (cm), filled grains panicle-1, unfilled grains panicle-1, growth duration (days) and grain yield (tha-1). Coefficient of variation (genotypic and phenotypic) was noticed high for most traits that revealed high variability among the studied genotypes. Broad-sense heritability ( ) was high in all traits except flag leaf breadth. Analysis of the cluster and its mean comparison showed that cluster 2 (i.e. BRRI 11B, BRRI 99B, IR 79125B and IR 79156B) represented the best agronomic traits and yield potentials. Therefore, selection of genotypes with valuable attributes from cluster 2 will be considered for maintainer line improvement programs. The use and estimation of predicted genetic gain will provide a visionary insight of the future genotypes produced after the crossing of the genotypes under study. Bangladesh Rice J. 26 (1): 69-78, 2022